HUBUNGAN POLA ASUH ORANG TUA DENGAN INTENSITAS PEMAKAIAN GADGET PADA ANAK PRASEKOLAH DI TK X KOTA BEKASI - Ratih Bayuningsih; Ridho Ilahi Ridho Ilahi (Journal Of Midwifery And Nursing Studies, 2023)
Entering the 21st century, the world is experiencing a very rapid development of information technology, known as digital growth or the digital era. In the digital era, you really need an updated smartphone or gadget to be able to keep up with technological advances. The gadget itself is a special electronic feature that has its own characteristics compared to other electronic features. Today's gadget users are not only teenagers and adults but also children. The purpose of this study was to analyze the relationship between parenting patterns and the intensity of gadget use in preschool children in TK X Bekasi City. The sample of this study was 62 respondents using total sampling. The design of this study used a cross sectional where the independent variable (parental care) and the dependent variable (intensity of gadget use) were collected at the same time, and were observed only once. The results of this study indicate that there is no relationship between parenting and the intensity of gadget use in preschool children in Kindergarten X Bekasi City with a p value of 0.791 and an odd ratio of 1.326, this happens because there are many other factors that influence children to use gadgets other than parenting. Recommendations from researchers for further research are to examine other factors that cause children to use gadgets. Keywords: Parenting, Intensity of Gadget Use, Preschoolers